1976
DOI: 10.1002/chin.197638142
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ORGANOMETALLIC CHEMISTRY. VI. MEERWEIN REACTION. IV. MECHANISTIC ASPECTS

Abstract: Die Rolle von Cu‐Salzen als Katalysatoren bei der Arylierung nach Meerwein wird untersucht [Substrate sind Cyclooctadien (COD), Allylalkohol u.a. Allylderivate sowie 4‐Butenol‐(l); als Arylierungsreagenz dient p‐Chlorbenzoldiazoniumchlorid].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The mechanism for the formation of 8 shown in Scheme 2 is supported by earlier studies by Levisalles 33 and Citterio, 34 who described the ability of arenediazonium ions such as 9 to act as nitrogen-centered radical scavengers for alkyl radicals such as 10. 35 Levisalles 33 had even obtained similar compounds to 8 as byproducts in mechanistic studies on the Meerwein arylation. The effective formation of diazonium ions from initiator 6 under our conditions was confirmed by an azo coupling reaction with 2-naphthol.…”
Section: Syn Lettsupporting
confidence: 58%
“…The mechanism for the formation of 8 shown in Scheme 2 is supported by earlier studies by Levisalles 33 and Citterio, 34 who described the ability of arenediazonium ions such as 9 to act as nitrogen-centered radical scavengers for alkyl radicals such as 10. 35 Levisalles 33 had even obtained similar compounds to 8 as byproducts in mechanistic studies on the Meerwein arylation. The effective formation of diazonium ions from initiator 6 under our conditions was confirmed by an azo coupling reaction with 2-naphthol.…”
Section: Syn Lettsupporting
confidence: 58%
“…The ability of diazonium salts to act as radical scavengers for nucleophilic alkyl radicals was first discovered in mechanistic studies on the Meerwein arylation [96]. Shortly after, this concept was applied for the functionalization of a limited group of activated alkenes [97][98][99].…”
Section: Carboamination Reactionsmentioning
confidence: 99%
“…by Levisalles and Rudler. 38 The formation of aryl-alkyl azo compounds as byproducts in classical copper(II) chloride mediated Meerwein arylations thereby demonstrated that diazonium ions can not only act as aryl radical sources, but also as scavengers for the alkyl radical intermediates 4 (Scheme 1). Further development of this reaction type towards a broadly applicable synthetic method was possible through the use of titanium(III) chloride 39 or iron(II) sulfate 13c,40 as reductant.…”
Section: Short Review Syn Thesismentioning
confidence: 99%